The perception of Engineering students toward teaching performance on online learning during COVID-19 pandemic - Teodoro Díaz-Leyva; Carlos Dávila-Ignacio; Jorge Sanchez-Ayte; Orlando Ortega-Galicio; Soledad Olivares-Zegarra; Nestor Alvarado-Bravo; Salvador Trujillo-Perez; Almintor Torres-Quiroz; José Razo-Quispe; Florcita Aldana-Trejo (Institute of Advanced Engineering and Science, 2022)
This study analyzed the perception of Mechanical Engineering and Systems Engineering students in the process of evaluating teacher performance in online teaching due to the COVID-19 pandemic. This was descriptive-correlational research. The results showed that the Systems Engineering students performed a better perception with the class session management factor and low qualification to the didactic strategies factor. Likewise, the Pearson correlation test indicated a significant relationship (0.000) between the specific factors on the overall performance factor. The topic factor has the greatest strength on the qualification of the overall performance factor, with a constant Pearson's correlation of 0.964. The Mechanical Engineering students showed a better perception with the class session planning factor and low qualification to the didactic strategies factor. Likewise, the Pearson correlation test indicated a significant relationship (0.000) between the specific factors on the overall performance factor. The didactic strategies factor being the one that has the greatest strength on the qualification of the overall performance factor, with a correlation constant Pearson's of 0.983.